STANDARDIZED NUTRITIONAL CARE PROCESS FOR SEVERE MALNUTRITION DUE TO CHRONIC DISEASE IN A PATIENT WITH LCH ON CHEMOTHERAPY, FEBRILE NEUTROPENIA, ANEMIA, AND PNEUMONIA - Deri Putra (Poltekkes Kemenkes Bengkulu, 2026)
Langerhans Cell Histiocytosis (LCH) is a rare disease caused by the abnormal proliferation of Langerhans cells that can affect multiple organs. This case report documents the standardized nutritional care process for a 3-year-old female patient (An. K) diagnosed with LCH on chemotherapy, febrile neutropenia, anemia, and pneumonia, admitted to the Aster Ward of RSUD Prof. Dr. Margono Soekarjo Purwokerto. Nutritional screening using the Pediatric Yorkhill Malnutrition Score (PYMS) yielded a total score of 5, indicating high malnutrition risk. Nutritional assessment revealed severe malnutrition (BB/TB: -3.02 SD; BB/U: -4.61 SD; TB/U: -4.32 SD) and inadequate oral intake (energy 17.6%, protein 38.7%, fat 25.4%, and carbohydrate 10.9% of requirements based on 24-hour recall). Nutritional diagnoses established were inadequate oral intake (NI-2.1) and severe malnutrition due to chronic disease (NC-4.2.1). Nutritional intervention was delivered through a high-calorie high-protein (TKTP) diet in soft food form, 3 main meals plus 1 snack per day, supplemented with Pediacomplate 20g/day. Oral nutrition support, nutrition education and counseling were also provided to the patient and family. After four days of monitoring, intake reached 65.2% of requirements, with a progressive daily increase. Hemoglobin improved from 6.7 g/dL to 11.2 g/dL and hematocrit from 18.8% to 32.1% following medical management. This case highlights the critical role of standardized nutritional care in managing severely malnourished oncology patients undergoing chemotherapy.